Uji Analisis Tingkat Kematangan dan Metode Perendaman terhadap Aspek Fisik dan Kimia Lada Putih (Muntok White Pepper) - Riwan Kusmiadi; Sitti Nurul Aini; Nurkholis Nurkholis (Universitas Bangka Belitung, 2017)
One of the problems an industrial pepper in Indonesia is the lower quality of production by the farmers. To overcome these problems we must have to do research to get a good technique in pepper processing and the good quality of pepper in accordance Indonesian National Standard. This research using a factorial randomized block design with three replications of two treatment factors. The first factor is physiologic mature (M) and the second factor is the soaking method (P). The research phase includes the preparation of tools and materials. Soaking pepper, cleaning the skin and stems, drying and analysis of pepper quality test. Changes observed in this research is the content of water, the level of colored pepper, and the levels of mold contamination. The result of this research shown the mature physiologically significant effect on the levels of pepper blackish in color and content of seeds lightly. Pepper levels blackish color shown on the highest passing phase that is optimum ripe 0.12% and the lower passing phase optimum ripe is 0.01%. The highest levels of seed lightly on shown at the mature phase towards optimum ripe 1.66% and the lower it show through the mature phase that is 0.71%. White pepper research results both in treatment and in the treatment of physiologically mature immersion method meet the Indonesian National Standard.